Switch off policies in job-shop manufacturing systems including workload evaluation. Issue 4 (2nd October 2021) - Renna, Paolo; Materi, Sergio
ABSTRACT: Energy efficiency is more relevant in the last years and drives enterprises to increase the efficiency of the manufacturing systems. This paper proposes switch-off policies to reduce energy consumption in job shop systems when the machines are in idle state. The model proposed uses the workload approach studied in the literature to take into account the relationships among the machines where the routing of the parts is random. The model proposed use the combination of direct and indirect workload of the machines to support the decisions on switch off/on. A simulation model is developed to test the proposed policies compared to another one presented in the literature. The main results highlighted how the model found in the literature for production lines can be efficiently adapted in the job-shop context. The proposed methods lead to a better compromise between energy-saving and lead time reducing the number of switch-off. This study has proposed a novel model to reduce energy consumption in manufacturing systems and the findings derived from the numerical analysis have provided an extended knowledge sustainable job-shop systems literature.